Harmonic Elimination Method for Permanent Magnet Synchronous Motor Utilizing Active Disturbance Rejection Control - Marwan Kanaan Ismael; Saif Talal Bahar; Ahmed Aizaldeen Abdullah (Proceedings of Engineering and Technology Innovation, 2025)
This study investigates the control of permanent magnet synchronous motor (PMSM) as the core component of speed control systems. The extensive employment of PMSMs in electric cars is ascribed to their efficiency, simplicity, dependability, and stable performance. Therefore, this article suggests an active disturbance rejection control (ADRC) strategy for electric motor control systems to improve the system’s robustness, accelerate response speed, and enhance tracking performance. The implementation of ADRC reduces the speed response time from 0.14 s to 0.04 s and the three-phase current drop time from 0.03 s to 0.01 s. The total harmonic distortion (THD) under the existing proportional-integral (PI) speed controller and the suggested ADRC speed controller are 10.58% and 5.73%, respectively, with the proposed ADRC having a reduced THD.